Temperature‐dependent luminescence of Tb3+ and Eu3+ single‐doped glasses for LED applications. Issue 12 (10th September 2015) - Loos, Sebastian; Steudel, Franziska; Ahrens, Bernd; Lee Leonard, Russell; Johnson, Jacqueline Anne; Schweizer, Stefan
Abstract: Tb 3+ and Eu 3+ single‐doped barium borate glass and ZBLAN glass are investigated for their photoluminescence (PL) and absolute PL quantum efficiency. In addition, both glass systems are characterized with respect to their color stability in the temperature range from 25 °C to 400 °C. The Tb 3+ doped glass shows high color stability over the entire temperature range investigated, whereas the Eu 3+ doped glass changes its color appearance with increasing temperature: Eu 3+ in ZBLAN glass changes its color appearance from the orange to the red spectral range, whereas the color appearance in borate glass is shifted from the red to the orange‐red spectral range. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)